Theory and Method in Higher Education Research - Huisman, Jeroen; Tight, Malcolm (Theory and Method in Higher Education Research Ser., 2020)
This volume of Theory and Method in Higher Education Researchcontains analyses and discussions of, amongst others, relational working, corpus linguistics, data dialogues, instrumental variables, participatory pedagogy, diverse participation, policy discourse, quality management and knowledge structures of research.